Progress towards the UN Commission on Life Saving Commodities recommendations after five years: a longitudinal assessment - Bennett Nemser; Diana Sera; Nora Springstubb; Paul Pronyk; Howard S Friedman; Theopista Kabuteni; Asia Hussein; Kyaw Aung; Felister Bwana; Nicholas Addofoh; Miriam Musa; Pascal Bijleveld; et al. (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background In 2012, the UN Commission on Life Saving Commodities (UNCoLSC) articulated a series of recommendations to expand access to 13 life-saving reproductive, maternal, newborn and child health (RMNCH) commodities with the greatest potential to reduce preventable deaths. We conducted a five-year longitudinal assessment of progress towards achieving these recommendations among countries in sub-Saharan Africa and Southeast Asia. # Methods Between 2013 and 2017, national reviews were undertaken at two time points among 14 countries with a high burden of preventable maternal-child deaths who were receiving support from a multi-UN agency RMNCH technical support and financing mechanism. Data were drawn from national health documentation (e.g. strategic plans, policies, guidelines); logistics management information systems; national household and health facility surveys; and interviews with governments and development partners. # Results Over time, the percent of health facilities with stock availability showed a statistically significant increase of five percentage points from 69% to 74% (median). Recent training at health facility also displayed a significant increase of eight percentage points from 38% to 46% (median). National RMNCH coordination mechanisms, treatment guidelines, and national training curricula and job-aids were near fully redressed. However, countries continue to face persistent supply chain challenges including national stock-outs, tracking commodities throughout the supply chain, and strengthening medicine control laboratories. # Conclusions While substantial progress has been made in improving access to life-saving commodities, including stock availability and workforce training at health facilities, additional efforts are required to improve regulatory efficiency, enhance commodity quality and safety, and reduce supply chain fragmentation.